2013
DOI: 10.1371/journal.pntd.0002587
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Central Metabolism of the Bloodstream Forms of Trypanosoma brucei: Production of Acetate in the Mitochondrion Is Essential for Parasite Viability

Abstract: BackgroundThe bloodstream forms of Trypanosoma brucei, the causative agent of sleeping sickness, rely solely on glycolysis for ATP production. It is generally accepted that pyruvate is the major end-product excreted from glucose metabolism by the proliferative long-slender bloodstream forms of the parasite, with virtually no production of succinate and acetate, the main end-products excreted from glycolysis by all the other trypanosomatid adaptative forms, including the procyclic insect form of T. brucei.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 52 publications
5
124
0
Order By: Relevance
“…Indeed, a recently developed metabolite profiling assay showed that threonine is the main acetate source of procyclic trypanosomes (11,46). This approach is based on the ability of 1 H NMR spectrometry to distinguish 13 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recently developed metabolite profiling assay showed that threonine is the main acetate source of procyclic trypanosomes (11,46). This approach is based on the ability of 1 H NMR spectrometry to distinguish 13 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For 1 H NMR analyses of glucose and threonine metabolism, 10 8 T. brucei procyclic cells were collected by centrifugation at 1,400 ϫ g for 10 min, washed once with PBS, and incubated for 6 h at 27°C in 5 ml of incubation buffer (PBS supplemented with 5 g/liter of NaHCO 3 , pH 7.4) containing D-[U- 13 C]glucose (4 mM) and threonine (4 mM). 50 l of maleate (20 mM) were added as an internal reference to a 500-l aliquot of the collected supernatant, and 1 H NMR spectra were performed at 500.13 MHz on a Bruker DPX500 spectrometer equipped with a 5-mm broadband probe head as described before (11,46 . In both NMR analyses, the integrity of the cells during the incubation was checked by microscopic observation.…”
Section: Nmr Analysis Of Excreted End Products From Glucose and Threomentioning
confidence: 99%
“…PrPta II 1 activity in the acetyl-CoA-forming direction was measured by monitoring the increase in absorbance at 233 nm due to thioester bond formation (ε 233 ϭ 5.55 mM Ϫ1 cm Ϫ1 ) (20,21). The reaction mixture contained 50 mM Tris (pH 7.5), 20 mM KCl, 20 mM NH 4 Cl, and 1 mM dithiothreitol (DTT), and the concentrations of acetyl phosphate and CoA were varied. Activity in the acetyl phosphate-forming direction was measured with two different assays.…”
Section: Methodsmentioning
confidence: 99%
“…A cetate production has been studied for many years in bacteria but has received less attention in eukaryotic microbes, even though acetate is produced as an important end product of energy metabolism in yeasts (1-3) and protists (4)(5)(6). Four different pathways for production of acetate from acetyl-coenzyme A (CoA) have been identified in eukaryotic microbes (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation